2022
DOI: 10.1111/1744-1633.12555
|View full text |Cite
|
Sign up to set email alerts
|

Hemithyroidectomy vs. total thyroidectomy for minimally invasive follicular thyroid carcinoma: Quality of life and oncological outcomes

Abstract: Aim: To evaluate outcomes of patients following hemithyroidectomy (HT) vs. total thyroidectomy (TT) for minimally invasive follicular thyroid carcinomas (MI-FTCs).Patients and Methods: This is a retrospective analysis of 82 patients with unilateral MI-FTC that was conducted for cases operated between April 2015 and April 2019.A total of 42 and 40 patients were included in the HT and TT groups, respectively.The main outcomes were survival, metastasis and recurrence rates; procedurerelated complications and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 26 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…In this review, we identified 20 studies reporting on physical HrQoL following TT or HT [ 18 , 34 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 67 , 68 , 70 , 73 ] ( Table 5 ). Eight studies compared postoperative TT HrQoL with community reference values using seven different QoL instruments (i.e., SF-36, MFI-20, ThyPRO, PSQI, Billewicz Score, visual analog scale, and 15D) [ 18 , 34 , 51 , 53 , 55 , 58 , 61 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this review, we identified 20 studies reporting on physical HrQoL following TT or HT [ 18 , 34 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 67 , 68 , 70 , 73 ] ( Table 5 ). Eight studies compared postoperative TT HrQoL with community reference values using seven different QoL instruments (i.e., SF-36, MFI-20, ThyPRO, PSQI, Billewicz Score, visual analog scale, and 15D) [ 18 , 34 , 51 , 53 , 55 , 58 , 61 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, nine studies directly compared physical-related HrQoL for patients undergoing TT versus HT using six different questionnaires (EORTC-QLQ-C30, EORTC-QLQ-THY34, SF-36, THYCA-QoL, FoP-Q-SF, and KT-QoL) [ 52 , 56 , 57 , 59 , 60 , 62 , 64 , 65 , 67 ]. Four of these studies found decreased physical-related HrQoL following TT compared with HT for at least one of the following items: global physical subscale ( n = 1), voice symptoms ( n = 1), sensory symptoms ( n = 1), neuromuscular symptoms ( n = 1), vitality ( n = 1), and problems with scar ( n = 1) [ 57 , 59 , 64 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations